Recent development of nanomaterials for carbon dioxide electroreduction. Issue 1 (30th March 2022) - Su, Jianjun; Liu, Yong; Song, Yun; Huang, Libei; Guo, Weihua; Cao, Xiaohu; Dou, Yubing; Cheng, Le; Li, Geng; Hu, Qiushi; Ye, Ruquan
Abstract: Electrochemical CO2 reduction reaction (CO2 RR) to produce value‐added products has received tremendous research attention in recent years. With research efforts across the globe, remarkable advancement has been achieved, including the improvement of selectivity for the reduction products, the realization of efficient reduction beyond two electrons, and the delivery of industrially relevant current densities. In this review, we introduce the recent development of nanomaterials for CO2 RR, including the zero‐dimensional graphene quantum dots, two‐dimensional materials such as metal chalcogenides and metal/covalent organic framework, single‐atom catalysts, and nanostructured metal catalysts. The engineering of materials into three‐dimensional structure will also be discussed. Finally, we will provide a summary of the catalytic performance and perspectives on future development. Abstract : Here, we review the recent development of nanostructured materials for CO2 reduction reaction, including the graphene quantum dots, metal chalcogenides, porous organic materials, single‐atom catalysts, nanostructured metals, and their structural engineering into three‐dimension skeletons.